Luís Dill e a narrativa para jovens : o gênero policial - Fajardo, Andressa (2014)
Brazilian literature for teenagers from the latest decades, being a subsystem different from the one for children, has displayed different themes and forms, including revitalization of classic genres such as detective novels, establishing a closer relationship between young readers and the mentioned production. From this perspective, we aim, throughout this dissertation, supported by different theories and researchers, to observe and discuss ways of appropriation of typical elements of the detective narrative in ten books by Brazilian writer Luís Dill. The theory of this research includes studies on the origins of the detective novel, its different textual modalities (mystery, black and suspense novel), based on studies of Todorov (1979), Medeiros and Albuquerque (1979), Reimão (1983), Boileau and Narcejac (1991), Chandler (2002), Carvalho (2006), among others who were of almost importance to that we could establish points of contact between the detective genre and the contemporary narratives analyzed. Furthermore, we also made use of theories on Reading sociology, especially through the contributions of Escarpit (1974, 1977), Barker and Escarpit (1975), Candido (1976), Hauser (1977), Aguiar (1996), Zilberman (2001) and views on the role of the cultural industry over the production and advertising of books based on studies carried out by Wellershoff (1970), Bourdieu (1974), Eco (1979), Lajolo and Zilberman (1988) and Horkheimer and Adorno (1990). As a result, it can be highlighted the fact that the relationship between the detective narrative and literature for teenagers is formed from the use of themes involving violence (death, violence, crimes etc.) to the way the literary work is constructed, the atmosphere full of mystery and investigations, the use of young characters in the role of detective and;/or criminal, clues to be investigated, a crime going on, among other factors which are responsible not only to approximate both esthetic objects, but also to provide the young reader, when comparing the real and the fictitious world, with the opportunity to question situations and emotions which make them individuals who are part of the world.